Dictionary of human resources and personnel management - Collin, P. H. (Peter Hodgson) (A & C Black, 2006)
This dictionary offers over 6,000 key terms covering all aspects of human resources, including recruitment and selection, appraisals, payment systems, dismissals and industrial relations.